2002
DOI: 10.1002/cncr.10678
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial comparing cyclophosphamide, methotrexate, and 5–fluorouracil (CMF) with rotational CMF, epirubicin and vincristine as primary chemotherapy in operable breast carcinoma

Abstract: BACKGROUNDAccording to the overview of Early Breast Cancer Trialists' Collaborative Group, anthracycline containing regimens are superior to cyclophosphamide, methotrexate, and 5–fluorouracil (CMF) as adjuvant chemotherapy for breast carcinoma, but no comparative information is available in terms of primary chemotherapy. In the current randomized controlled trial, the authors compared CMF with a chemotherapy regimen including CMF, epirubicin, and vincristine (CMFEV).METHODSTwo hundred eleven patients with Stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
11
0
2
Order By: Relevance
“…These differences in terms of recurrence and death, although not statistically significant, offer evidence of a potential major efficacy of the CMFEV compared to the CMF regimen. This efficacy was, at least in part, more clearly showed in our previous study on neo-adjuvant chemotherapy where, on a short term evaluation, the rate of clinical responses, both complete (CR) and complete plus partial (PR), were significantly higher in the subset of pre-menopausal patients treated with CMFEV compared to those treated with CMF [10]. Similarly, on a long-term evaluation, again in the subset of pre-menopausal patients, the proportion of RFS tended to be higher and the proportion of LRRFS was significantly higher in the CMFEV arm compared to the CMF arm, thus mirroring the short-term response results [11].…”
Section: Cmfev Regimen Versus Cmf Regimen: Efficacy Relationship Witmentioning
confidence: 58%
See 4 more Smart Citations
“…These differences in terms of recurrence and death, although not statistically significant, offer evidence of a potential major efficacy of the CMFEV compared to the CMF regimen. This efficacy was, at least in part, more clearly showed in our previous study on neo-adjuvant chemotherapy where, on a short term evaluation, the rate of clinical responses, both complete (CR) and complete plus partial (PR), were significantly higher in the subset of pre-menopausal patients treated with CMFEV compared to those treated with CMF [10]. Similarly, on a long-term evaluation, again in the subset of pre-menopausal patients, the proportion of RFS tended to be higher and the proportion of LRRFS was significantly higher in the CMFEV arm compared to the CMF arm, thus mirroring the short-term response results [11].…”
Section: Cmfev Regimen Versus Cmf Regimen: Efficacy Relationship Witmentioning
confidence: 58%
“…Indeed in the first study, the superiority of CMFEV regimen, as short term objective response, was seen only in premenopausal and not in post-menopausal patients; in addition, in a multivariate analysis, a significant interaction was confirmed between the menopausal status and the type of treatment on the probability to obtain CR or CR plus PR [10]. In the present study, a significant correlation was observed between the estrogen and/or progesterone receptor status and the type of regimen; CMFEV was more effective, in terms of OS and RFI, in patients with positive ER and/or PgR tumors but not in patients with both negative ER and PgR tumors.…”
Section: Cmfev Regimen Versus Cmf Regimen: Efficacy Relationship Witmentioning
confidence: 94%
See 3 more Smart Citations